2004
DOI: 10.1103/physrevlett.92.067001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Determination ofHc2under Accurate Alignment in(TMTS

Abstract: Cantilever magnetometry has been used to measure the upper critical magnetic field H c2 of the quasi-one dimensional molecular organic superconductor (TMTSF) 2 ClO 4 . From simultaneous resistivity and torque magnetization experiments conducted under precise field alignment, H c2 at low temperature is shown to reach 5T, nearly twice the Pauli paramagnetic limit imposed on spin singlet superconductors. These results constitute the first thermodynamic evidence for a large H c2 in this system and provide support … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
94
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 23 publications
10
94
1
Order By: Relevance
“…32) In (TMTSF) 2 ClO 4 , Oh et al found that H c2 exceeds H P at low temperatures. 33) Recently, Yonezawa et al discovered a shift in the principal axis of the in-plane field-angle dependence of the superconducting onset temperature, which may be related to the FFLO state. In this system, a singlet state with line nodes (the so-called d-wave state) is considered to be likely.…”
Section: Introductionmentioning
confidence: 99%
“…32) In (TMTSF) 2 ClO 4 , Oh et al found that H c2 exceeds H P at low temperatures. 33) Recently, Yonezawa et al discovered a shift in the principal axis of the in-plane field-angle dependence of the superconducting onset temperature, which may be related to the FFLO state. In this system, a singlet state with line nodes (the so-called d-wave state) is considered to be likely.…”
Section: Introductionmentioning
confidence: 99%
“…(12). If we do this and if we introduce more convenient variables, y = y, y 1 = y + vy (py) vF z, we can rewrite Eq.…”
mentioning
confidence: 99%
“…Our analysis of Eq. (12) shows that the RS phase may appear only at magnetic fields of the order of 50 T , where superconductivity is already destroyed by the paramagnetic spin-splitting effects. Therefore, for a magnetic field parallel to the conducting axis, H a, unlike the situation, where it is perpendicular to it, H b ′ [18][19][20][21][22][23], we can ignore the above mentioned RS effects.…”
mentioning
confidence: 99%
See 2 more Smart Citations